Long-Term Outcomes of Massive Rotator Cuff Tear Repair: A Systematic Review. Issue 1 (February 2022) - Shah, Nihar S.; Suriel Peguero, Emil; Umeda, Yuta; Crawford, Zachary T.; Grawe, Brian M
Background: With an increase in the treatment options available for massive rotator cuff tears, understanding the long-term outcomes of the chosen modality is important. Questions/Purpose: The purpose of this study was to systematically review the available literature on repair of massive rotator cuff repairs and learn the longevity of outcomes, the failure rate, outcomes after failure, and any contributing factors to poor outcomes or failure. Methods: We conducted a systematic review of the MEDLINE, Cochrane, and Embase databases to find studies that investigated the long-term results of repair of massive rotator cuff repairs. Studies were excluded if they did not stratify results of massive tears, provide a definition for a massive rotator cuff tear, or report isolate patients with long-term follow-up. Results: Six studies met the inclusion criteria, for a total of 472 shoulders; average patient age was 57.6 years. Follow-up ranged from 119 to 240 months. Outcome scores improved significantly following repair and were maintained throughout follow-up. The repair failure rate across studies was 39.2%. Patients who suffered retear had significantly worse outcome scores than patients with intact tendons at long-term follow-up. Conclusions: The existing literature on long-term follow-up after massive rotator cuff repair is scarce and not of high level of evidence. This review found repair of massive rotator cuff tears leads to long-term maintained improvements in outcome measures. Failure of repair is quite common, but results following failure are superior to preoperative outcomes.